A Holistic Goal in Learning English: Case Study on English Club of Junior High School - Hanafi, Syahrul (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
The objective of this study is to examine the English Club of a Junior High School students' integrative motivation. The purpose of this research is to collect data on the students' integrative motivation to learn English in a Junior High School. Qualitative methods including observation, interview, and documentation were employed in this study. Understanding the pupils' integrative motivation for learning English was the main objective. The results show that many students would benefit from speaking with native speakers to improve their English proficiency. Out of the total number of students, six aim to enhance their listening, reading, writing, and speaking abilities in English. One student specifically wants to speak with native speakers. Improving one's oratory abilities is a goal of many students. The pupils' interest in learning about the development of English phonetics, pronunciation, and word order led them to study the language.